2021
DOI: 10.1021/acs.orglett.0c03990
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of PD-116740

Abstract: A new approach was developed to achieve the asymmetric total synthesis of (+)-PD-116740, an angucyclinone from the actinomycete isolate (WP 4669). A sequence of asymmetric dihydroxylation followed by oxidative cyclization was applied to stereoselectively construct the core trans-9,10-dihydrophenanthrene-9,10-diol B–C–D ring. A new Cu salt Cu­(OH)­OTf·NMI2 was found to be the best oxidant to induce the oxidative coupling and phenol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…There are several approaches through metabolic engineering, including heterologous expression of entire gene clusters, engineering regulatory networks, gene insertions and deletions, redirecting metabolic pathways, stimulating by precursors, and genetic knocking out of loci. In S. rimosus NRRL 3016, heterologous expression of entire gene clusters was successful in manufacturing secondary metabolites such as tetrangulol and tetrangomycin (Zheng et al, 2021). In another case, the genes responsible for Ralstonia eutropha's polyhydroxy butyrate (PHB) biosynthesis pathway were transferred to Saccharomyces cerevisiae, a more practical organ-ism for industrial application (Thu et al, 2023).…”
Section: Metabolic Engineering Approaches To Improve Bioremediationmentioning
confidence: 99%
“…There are several approaches through metabolic engineering, including heterologous expression of entire gene clusters, engineering regulatory networks, gene insertions and deletions, redirecting metabolic pathways, stimulating by precursors, and genetic knocking out of loci. In S. rimosus NRRL 3016, heterologous expression of entire gene clusters was successful in manufacturing secondary metabolites such as tetrangulol and tetrangomycin (Zheng et al, 2021). In another case, the genes responsible for Ralstonia eutropha's polyhydroxy butyrate (PHB) biosynthesis pathway were transferred to Saccharomyces cerevisiae, a more practical organ-ism for industrial application (Thu et al, 2023).…”
Section: Metabolic Engineering Approaches To Improve Bioremediationmentioning
confidence: 99%
“…Owing to the biological significance of heterocycle-containing antibiotics, various research groups have reported different methodologies for their synthesis. However, Zheng et al [ 81 ] in 2021 devised a facile route for the synthesis of PD-116740 involving Sharpless asymmetric dihydroxylation and oxidative cyclization. In the first step, quinone was subjected to sodium hydrosulfite followed by protection of the –OH group by benzyl bromide, which gave 138 in 91% yield.…”
Section: Review Of the Literaturementioning
confidence: 99%